THE STUDY OF GREEN OPEN SPACE IN TANGERANG - Aditianata; Setiawan, Chandra; Martini, Elsa; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
Increasing urban land demand is in line with population growth, causing high urban land use change. including Green Open Space is decreasing. A city should consider the existence of green open space to be improved in its function and role as a forum for the community to interact socially with fellow citizens and visitors, while also playing a role in creating a balanced urban face environment. The increasing need for urban land is a consequence of the city’s rapid development and development as accommodation for the city’s development and development. Land - land that is converted into a developed area is a potential vacant land to be developed, both in the form of productive land and non-productive land. As a result, open land is increasingly pressed and narrow.